Parental Self-Efficacy in Educating Elementary School Children - Yosef, Yosef; Hasmalena, Hasmalena; Sucipto, Sigit Dwi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The main purpose of this study was to explore the belief that parents were able to perform or to manage tasks effectively related to parental involvement in educating elementary school children. 60 parents of elementary school children participated in this study, consisting of 20 fathers and 40 mothers. They were selected randomly from two public elementary schools and fulfilled informed consent showing they participated voluntarily in the study. The Parents Self Efficacy Scale which has been tested for validity and reliability administered to the parents. This self-report instrument, which consists of 68 questions asked parents to respond six aspects of the scale, namely the ability to parent children, communicate with the school/teacher, help children learn at home, become school volunteers, make decisions, and collaborate with the community. The results showed that parents have a high level of efficacy in all six aspects. However, among the six aspects, the higher level of parental self-efficacy was parenting children, communicating with the school/teacher, helping children learn at home. Meanwhile, parental self-efficacy of becoming school volunteers, making decisions, and collaborating with the community were lower that the first three